Research on the Applicability of Hybrid RANS/LES Models to Predict the Flow Behavior in Bulb Tubular Pump Under Rated and Stall Conditions - Longyue Sun; Qiang Pan; Linlin Geng; Desheng Zhang; Xavier Escaler (Energy Science & Engineering)
ABSTRACT The investigation into the internal flow characteristics of the bulb tubular pump device has important practical significance for improving both optimal design and operation stability. This paper uses different RANS/LES turbulence models to conduct numerical simulation research on the bulb tubular pump model device, specifically focusing on the differences in internal flow characteristics under the small flow stall condition 0.5Qdes and the design condition 1.0Qdes. The macroscopic energy characteristics of different turbulence models are verified through experiment tests, revealing that the DDES turbulence model provides better predicted hydraulic performance under stall conditions. The numerical difference under low flow conditions is mainly due to the different degrees of turbulent flow field analysis, while the analysis degree of high‐efficiency flow rate conditions with uniform internal flow remains similar. The vortex identification method Omega is used to visualize the vortex structure characteristics of the time‐averaged flow field, uncovering large‐scale stall vortex structures under small flow conditions, with the blending RANS/LES turbulence model offering superior resolution of vortex structures. Furthermore, the paper deduces the calculation method of the RANS/LES turbulence model pulsation entropy production based on the SST turbulence model pulsation entropy production calculation formula. A comprehensive investigation of the local power loss characteristics of the main flow‐passing components—impeller, diffuser, and bulb—reveals that the blades and wall surfaces are the main contributors to increase in power losses. The comparison shows that the DDES turbulence model provides more accurate predictions of the hydraulic performance of stall conditions and visualizing flow field characteristics.